3-D reconstructions of active stars. (5th March 2015) - Korhonen, Heidi
Abstract: Stars are usually faint point sources and investigating their surfaces and interiors observationally is very demanding. Here I give a review on the state-of-the-art observing techniques and recent results on studying interiors and surface features of active stars.